THE IDENTIFICATION OF CENTRAL JAVA CLASSIC ERA’S ARCHITECTURE (BOROBUDUR AND PRAMBANAN, (9TH CENTURY) ON THE TEMPLE IN THE CAMBODIA’S TRASITIONAL ERA (BAKONG, 9TH CENTURY) MORPHOLOGICAL TYPOLOGY STUDIES (MASS ORGANIZATION, FLOOR PLAN, FIGURE AND ORNAMENTS) - Pratomo (Jurnal Riset Arsitektur, 2018)
Abstract- Architectural temples of the middle classical era such as Prambanan and Borobudur temples are thought to have inspired the temples in Indochina. It has become a common guess both among the tour guides in Cambodia or the researchers who reviewed the Khemer Kingdom Architecture. The existence of the relationship between the temple in Java and the temple in Cambodia is possible because Jayawarman II, who later build the kingdom of Khemer, once lived in Java when large middle classical temple style architecture was built. To find out the architectural connections of temples in Java and in Cambodia then the first thing to do is to know all the architectural unsurts in both temples. So the purpose of this study is to know the unsurts of spatial, plan, figures and temple ornaments of the middle classical era of Java and pre-Angkor temple era. This research is done by qualitative method of comparative. Qualitative research is applied by visiting and observing physical objects, then discussed using theories relating to research topics. While the object is selected using purposive sampling method, with the basic object of research is closely related to the style, wholeness and scale. Of the 80 points used in identifying architectural unsurts in the mass structure, floor plan, figures, and ornaments, the authors found 13 very similar points, 50 points to Bakong but not similar, and 17 points missing from Bakong. Based on these results the allegation that the temple of the middle classical era of Java has a relationship with the transitional era are becoming stronger. Key Words: morphology, architectural elements, Borobudur, Prambanan, Bakong